Influence Application of Learning Models Problem Based Learning (PBL) Against Results Study Mathematics Student Class VII SMP Negeri 1 Pangkur - Chintia Inka; Budi Sasomo; Anwas Mashuri (MultiTech Publisher, 2023)
This research aims to determine the effect of the Problem Based learning model Learning (PBL) on student learning outcomes in Mathematics class VII SMP Negeri 1 Pangkur . This research is experimental research. Where is the population of This research consisted of 7 class VII students of SMP Negeri 1 Pangkur. Meanwhile, the sample from this research was an experimental group from class VII F with PBL model totaling 2 8 students and the Control Class group from class VII G which totaling 2 8 students. The data collection technique used in this research is observation , test And documentation . From the test carried out at the last meeting, a Significant value was obtained test